Application of the Law to Penal Legal Measures in Investigations of Perpetrators of Online Gambling Crimes (Case Study LP/A-05 /Iii / 2023 / Spkt / Satreskrim / Res Mura / South Sumatera in the Legal Area of the Police - Muhammad Feryal Kautsar; Ruben Achmad; Abdul Latif Mahfuz (Universitas Labuhanbatu, 2024)
The world is currently developing rapidly along with technological advances, where existing technological advances are developing rapidly and are needed by society in everyday life. Another form of technological development is the use of social media. This research is a form of empirical method research. Empirical research is based on primary data (results of research in the field). The problem is the factors that influence the application of penal measures in the investigation of perpetrators of online gambling crimes (Case Study LP/A-05 /III / 2023 / SPKT / Satreskrim / Res Mura / South Sumatra in the Musi Rawas Police Legal Area). As a result, the factors that influence the implementation of penal legal measures are legal factors or statutory regulations, law enforcement factors, facilities and infrastructure factors and community factors